Acute inhalation lung injury secondary to zinc and copper aspiration from food contact dust. Issue 6 (9th June 2022) - Moss, James; Sinha, Aditi; Messahel, Shrouk; Grime, Christopher
Abstract : A previously healthy boy of preschool age was brought to the emergency department by ambulance with respiratory distress following the accidental inhalation of food contact dust (cake decorating powder). Prehospital oxygen saturations were 80% in room air. Initial treatment was with oxygen, nebulised salbutamol, oral dexamethasone and intravenous amoxicillin/clavulanic acid. Treatment was escalated to nasal high flow oxygen therapy and high dependency care within 8 hours. Lung fields on his initial chest X-ray were clear but the following day showed perihilar infiltrates extending into the lower zones in keeping with inflammation. He was treated with intravenous methylprednisolone, followed by a weaning dose of oral prednisolone over 14 days. He required oxygen therapy for 9 days and remained in hospital for 11 days. Outpatient follow-up, 24 days after the inhalation took place was reassuring with the child showing no signs of abnormal respiratory symptoms.